2020
DOI: 10.31235/osf.io/wr9jb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 on fertility plans in Italy, Germany, France, Spain and UK

Abstract: This study offers an overview on changes in fertility plan during the COVID-19 crisis of a representative sample of the young population (18-34) in Italy, France, Germany, Spain and UK. Data were collected between March 27 and April 7, 2020. Our results show that fertility plans have been negatively revised in all countries, but not in the same way. In Germany and France fertility plans changed moderately, with many people still planning or postponing their decision to have a child during the 2020. In Italy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
4
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 10 publications
4
75
4
7
Order By: Relevance
“…Likewise, the differencein-differences estimates (Table 1) are nonsignificant for both. This result is in line with findings from [9], which showed that fertility intentions during the lockdown decreased, although less so in France than Spain and Italy, mainly reflecting a postponement of fertility plans rather abandonment thereof. Notably, however, we do observe a significant 18 percent increase in such searches in France in the post-lockdown period.…”
Section: Plos Onesupporting
confidence: 91%
See 3 more Smart Citations
“…Likewise, the differencein-differences estimates (Table 1) are nonsignificant for both. This result is in line with findings from [9], which showed that fertility intentions during the lockdown decreased, although less so in France than Spain and Italy, mainly reflecting a postponement of fertility plans rather abandonment thereof. Notably, however, we do observe a significant 18 percent increase in such searches in France in the post-lockdown period.…”
Section: Plos Onesupporting
confidence: 91%
“…As such, we expect considerable heterogeneity across countries-and, in particular, between Europe and the United States-in the degree to which individuals and families experience economic uncertainty and hardship. This heterogeneity is also likely to be reflected in differences in the magnitude and direction of patterns of relationship formation, quality, and dissolution, as well as fertility plans, as a consequence of heterogeneity in lockdowns, economic conditions, and policy responses by country [9]. Specifically, we hypothesize that lockdowns will lead to fewer demographic consequences in countries that better managed the economic fallout from the pandemic and provided a stronger financial safety net.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implications of the pandemic and the associated containment measures on demography, society and economy are being the object of study for many researchers, who focused on direct consequences [15,13] as well as on indirect consequences [20,4,8]. Such implications also include impacts on the individuals' lifestyle and on their behaviors towards the community, that resulted in changes in the network of relations binding individuals to the people close to their everyday life, and in the availability of resources to exchange tangible and intangible support.…”
Section: Introductionmentioning
confidence: 99%